DETERMINATION OF MINIMUM EFFECTIVE DOSE OF ZINC CHLORIDE FOR MODULATION OF METABOLISM AND SILK PRODUCTION IN THE SILKWORM, BOMBYX MORI - S. KAVITHA; S. SIVA PRASAD; K. YELLAMMA (The Bioscan, 2011)
The minimum effective dose (MED) of zinc chloride for modulation of metabolism and silk production in Bombyx mori is determined by analyzing the changes in the protein profiles of silk gland, haemolymph, fat body and muscle. The step-down method with zero-dose control was employed to achieve the desired objective. The experimental samples included the silkworm larvae, fed with mulberry leaves soaked in different concentrations ZnCl2 solution (300μg, 200μg, 100μg, 50μg, 20μg, 10μg, 5μg, 2μg and 1μg) in distilled water, while the zero-dose control included those fed with normal mulberry leaves. The impact of zinc was analyzed in terms of day-to-day effect (changes on alternative days) and overall effect (fifth instar-end changes) on protein profiles. The doseresponse analysis showed that the effect of ZnCl2 on proteins is more pronounced at lower doses (1μg) in the silk gland and haemolymph and at higher doses in fat body (200μg) and muscle (20μg). Keeping in view, the impact of ZnCl2 on silk gland proteins, a minimum dosage @ 1μg /100 worms is suggested for positively modulating the metabolism and silk production in the silkworm.